Urban verticalization morphologies: applying the anatomies of density theory in three Chilean metropolitan areas - Vicuña Magdalena (Lodz University of Technology Press, 2023)
This work aims to visualize and analyze the anatomies of density proposed by Angel et al. (2021) in the context of verticalization in the metropolitan areas of Santiago, Valparaíso and Concepción between 2002 and 2021. As these authors suggest, cities obtain their density from different combinations of these seven factors. Our hypothesis is that the dynamic processes of verticalization in Chilean metropolitan areas are significantly reconfiguring the urban structure. To move towards more integrated and sustainable cities, it is necessary to understand in all its complexity the new spatial relationships and forms of density distribution derived from verticalization. We characterize verticalization with the data available on building permits between 2002 and 2021. To understand the territorial scope and intensity of verticalization, distribution maps of building permits are made, by year, in the three metropolitan areas. Based on the theory of the anatomies of density (Angel et al. 2021), we carried out a first density factorization on the metropolitan scale. Synthetic representations are made in three dimensions of density and three-time cuts: 2002, 2012 and 2020. Results focus on recent verticalization trends in AMS, AMV and AMC. The discussion addresses three main findings: From the center to peri-centralities: territorial expansion of verticalization, Densification Intensification and Diversified verticalization: anatomies of density at the metropolitan and municipal scale.
Keywords: verticalization; density; urban morphology; pionizacja; zagęszczenie; morfologia miast